The Effect of Health Education using “Module on Mental Health for Children and Adolescents” Media on Mental Health Knowledge of Health Cadres - Utami, Nurma Sri; Estria, Suci Ratna (Jurnal Keperawatan, 2024)
Detection of mental health in children and adolescents is essential for the next stage of growth and development, this is done to prevent and minimize disturbances so that when children and adolescents face problems, they can survive. The study aimed to determine the effect of health education using “Module on Mental Health for Children and Adolescents” media on the mental health knowledge of Health Cadres In Suro Village. This study used a pre-experimental design, one group pretest, and a posttest involving 40 health cadres in Suro Village in 2022. The total sampling technique was used because the population was less than 100. Data were collected using mental health knowledge questionnaires tested for validity and reliability by researchers. Univariate analysis was used to describe the characteristics of health cadres, and knowledge of cadres before and after health education. In contrast, bivariate analysis was conducted to determine health education’s effect on increasing knowledge of health cadres using the mental health module. The results showed that the majority of cadres were 25-36 years old (37.5%), the last education was junior high school (47,5%), they were housewives (70%), and the length of service as cadres was 1-10 years (60%). The Wilcoxon test results obtained a p-value of 0.000<0.05, meaning that there was a significant change in the level of knowledge after health education was carried out.  “Module on Mental Health for Children and Adolescents” can be used to increase mental health knowledge among Health Cadres.